MRI discriminates thrombus composition and ST resolution after percutaneous coronary intervention in patients with ST-elevation myocardial infarction. - Ignasi Barba (Public Library of Science (PLoS), 2011)
Histological composition of material obtained by thrombus aspiration during percutaneous coronary intervention (PCI) in patients with ST-segment elevation acute myocardial infarction (STEMI) is highly variable. We aimed to characterize this material using magnetic resonance imaging (MRI) and to correlate MRI findings with the success of PCI in terms of ST-segment resolution. Thrombus aspiration during primary or rescue PCI was attempted in 100 consecutive STEMI patients, of whom enough material for MRI was obtained in 59. MR images were obtained at 9.4T and T1 and T2 values were measured. Patients with (n = 31) and without (n = 28) adequate ST resolution 120 min after PCI (≥70% of pre-PCI value) had similar baseline characteristics except for a higher prevalence of diabetes mellitus in the latter (10 vs. 43%, p = 0.003). T1 values were similar in both groups (1248±112 vs. 1307±85 ms, respectively, p = 0.7). T2 values averaged 31.2±10.3 and 36.6±12.2 ms; in thrombus from patients with and without adequate ST resolution (p = 0.09). After adjusting for diabetes and other baseline characteristics, lower T2 values were significantly associated with inadequate ST resolution (odds ratio for 1 ms increase 1.08, CI 95% 1.01-1.16, p = 0.027). Histology classified thrombus in 3 groups: coagulated blood (n = 38), fibrin rich (n = 9) and lipid-rich (n = 3). Thrombi composed mostly of coagulated blood were characterized as being of short (n = 10), intermediate (n = 15) or long evolution (n = 13), T2 values being 34.0±13.2, 31.9±8.3 and 31.5±7.9 ms respectively (p = NS). In this subgroup, T2 was significantly higher in specimens from patients with inadequate perfusion (35.9±10.3 versus 28.6±6.7 ms, p = 0.02). This can be of clinical interest as it provides information on the probability of adequate ST resolution, a surrogate for effective myocardial reperfusion.